Ultrahigh Power Factor in Thermoelectric System Nb0.95M0.05FeSb (M = Hf, Zr, and Ti). Issue 7 (2nd May 2018) - Ren, Wuyang; Zhu, Hangtian; Zhu, Qing; Saparamadu, Udara; He, Ran; Liu, Zihang; Mao, Jun; Wang, Chao; Nielsch, Kornelius; Wang, Zhiming; Ren, Zhifeng
Abstract: Conversion efficiency and output power are crucial parameters for thermoelectric power generation that highly rely on figure of merit ZT and power factor (PF), respectively. Therefore, the synergistic optimization of electrical and thermal properties is imperative instead of optimizing just ZT by thermal conductivity reduction or just PF by electron transport enhancement. Here, it is demonstrated that Nb0.95 Hf0.05 FeSb has not only ultrahigh PF over ≈100 µW cm −1 K −2 at room temperature but also the highest ZT in a material system Nb0.95 M0.05 FeSb (M = Hf, Zr, Ti). It is found that Hf dopant is capable to simultaneously supply carriers for mobility optimization and introduce atomic disorder for reducing lattice thermal conductivity. As a result, Nb0.95 Hf0.05 FeSb distinguishes itself from other outstanding NbFeSb‐based materials in both the PF and ZT . Additionally, a large output power density of ≈21.6 W cm −2 is achieved based on a single‐leg device under a temperature difference of ≈560 K, showing the realistic prospect of the ultrahigh PF for power generation. Abstract : A material system Nb0.95 M0.05 FeSb (M = Hf, Zr, Ti) with an ultrahigh power factor (PF) around 100 µW cm −1 K −2 at room temperature is demonstrated. It shows a superior PF compared to other high‐performance thermoelectric materials within a wide temperature range. In this system, Nb0.95 Hf0.05 FeSb is noticeable for suppressing lattice thermal conductivity while the ultrahigh PF is maintained, contributing to a significantly improved figure of merit, ZT .